Contractual Interpretation, Registered Documents and Third Party Effects. Issue 4 (July 2014) - Barber, Matthew; Thomas, Rod
<x xml:space="preserve">Abstract</x> This article considers whether extrinsic material should be available in interpreting registered documents when these may be contractual in nature or relate to contractual agreements. Many registers, for example the current scheme for recording land title, are intended to facilitate the reliance of third parties on their content, an objective that suggests that extrinsic material should be excluded. Such an approach, however, could itself cause unfairness and conflicts with the way that contractual documents are normally interpreted. Exploring this question leads us to consider the contextual approach to contractual interpretation generally and whether it should take account of the contemplated effects of contractual language on third parties. After concluding in the affirmative, we then ask whether this is sufficient as an approach to interpreting contractual documents entered into a register.